Studies on Water–Aluminum Scrap Reaction Kinetics in Two Steps and the Efficiency of Green Hydrogen Production - Mezulis, Ansis; Richter, Christiaan; Lesnicenoks, Peteris; Knoks, Ainars; Varnagiris, Sarunas; Urbonavicius, Marius; Milcius, Darius; Kleperis, Janis (MDPI, 2023)
This work aims to explain aluminum hydrolysis reaction kinetics based on a properly chosen theoretical model with machined aluminum waste chips as well as alkali solutions up to 1M as a promoter and to estimate the overall reaction profit. The purpose of this work is to assess the optimal alkali concentration in the production of small- and medium-scale green hydrogen. To obtain results with better accuracy, we worked with flat Al waste chips, because a flat surface is preferable to maximally increase the time for the created hydrogen bubbles to reach the critical gas pressure. Describing the reaction kinetics, a flat shape allows for the use of a planar one-dimensional shrinking core model instead of a much more complicated polydisperse spheric shrinking core model. We analyzed the surface chemical reaction and mass transfer rate steps to obtain the first-order rate constant for the surface reaction and the diffusion coefficient of the aqueous reactant in the byproduct layer, respectively. We noted that measurements of the diffusion coefficient in the byproduct layer performed and discussed in this paper are rare to find in publications at alkali concentrations below 1M. With our reactor, we achieved a H2 yield of 1145 mL per 1 g of Al with 1M NaOH, which is 92% of the theoretical maximum. In the estimation of profit, the authors’ novelty is in paying great attention to the loss in alkali and finding a crucial dependence on its price. Nevertheless, in terms of consumed and originated materials for sale, the conversion of aluminum waste material into green hydrogen with properly chosen reaction parameters has positive profit even when consuming an alkali of a chemical grade. © 2023 by the authors. --//-- Mezulis A., Richter C., Lesnicenoks P., Knoks A., Varnagiris S., Urbonavicius M., Milcius D., Kleperis J.; Studies on Water–Aluminum Scrap Reaction Kinetics in Two Steps and the Efficiency of Green Hydrogen Production; (2023) Energies, 16 (14), art. no. 5554; DOI: 10.3390/en16145554; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85166176676&doi=10.3390%2fen16145554&partnerID=40&md5=ef6e4aed276993000c030ac11e1584e4. Published under the CC BY 4.0 licence.
Baltic Research Programme project No. EEA-RESEARCH-92, EEA Grant No. EEZ/BPP/VIAA/2021/5. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; alkali promoter; aluminum hydrolysis; aluminum waste; hydrogen production efficiency; reaction rate